2009
DOI: 10.1097/ta.0b013e3181a59ad5
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Early Mortality and Coagulopathy are Sustained Better in Patients With Blunt Trauma After Institution of a Massive Transfusion Protocol in a Civilian Level I Trauma Center

Abstract: In the civilian setting, aggressive use of FFP and platelets drastically reduces 24-hour mortality and early coagulopathy in patients with trauma. Reduction in 30 day mortality was only seen after blunt trauma in this small subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
268
0
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(284 citation statements)
references
References 12 publications
2
268
0
14
Order By: Relevance
“…Although there appears to be a clear reduction in mortality for injured soldiers, 10,[13][14][15]41 this finding has recently been questioned within the civilian cohort. 1,[21][22][23][24] Prior to the implementation of a formalized high plasma MTP (Table 1), mortality for patients who required a massive transfusion (≄ 10 units of RBCs) following grade 3, 4 or 5 hepatic injuries at our institution was 60%, 46% and 71%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Although there appears to be a clear reduction in mortality for injured soldiers, 10,[13][14][15]41 this finding has recently been questioned within the civilian cohort. 1,[21][22][23][24] Prior to the implementation of a formalized high plasma MTP (Table 1), mortality for patients who required a massive transfusion (≄ 10 units of RBCs) following grade 3, 4 or 5 hepatic injuries at our institution was 60%, 46% and 71%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…[32][33][34] This includes an immediate transfer to the operating theatre for hemorrhage control as the dominant guiding principle for improving the patient's probability of survival. The apparent success of "hypotensive resuscitation" in both the civilian and military contexts is also crucial.…”
Section: Initial Assessment and Resuscitationmentioning
confidence: 99%
“…Studies have confirmed the survival benefit of MTP. Dramatic reduction in many of the complications including organ failure has been observed in critically injured patients receiving massive transfusions [3,5,12,13].…”
Section: Massive Transfusion Protocol (Mtp)mentioning
confidence: 99%